Contribution of Type IV Pili to the Virulence of Aeromonas salmonicida subsp. salmonicida in Atlantic Salmon (Salmo salar L.) - Boyd, Jessica M. (American Society for Microbiology (ASM), 2008)
Aeromonas salmonicida subsp. salmonicida, a bacterial pathogen of Atlantic salmon, has no visible pili, yet its genome contains genes for three type IV pilus systems. One system, Tap, is similar to the Pseudomonas aeruginosa Pil system, and a second, Flp, resembles the Actinobacillus actinomycetemcomitans Flp pilus, while the third has homology to the mannose-sensitive hemagglutinin pilus of Vibrio cholerae. The latter system is likely nonfunctional since eight genes, including the gene encoding the main pilin subunit, are deleted compared with the orthologous V. cholerae locus. The first two systems were characterized to investigate their expression and role in pathogenesis. The pili of A. salmonicida subsp. salmonicida were imaged using atomic force microscopy and Tap- and Flp-overexpressing strains. The Tap pili appeared to be polar, while the Flp pili appeared to be peritrichous. Strains deficient in tap and/or flp were used in live bacterial challenges of Atlantic salmon, which showed that the Tap pilus made a moderate contribution to virulence, while the Flp pilus made little or no contribution. Delivery of the tap mutant by immersion resulted in reduced cumulative morbidity compared with the cumulative morbidity observed with the wild-type strain; however, delivery by intraperitoneal injection resulted in cumulative morbidity similar to that of the wild type. Unlike the pili of other piliated bacterial pathogens, A. salmonicida subsp. salmonicida type IV pili are not absolutely required for virulence in Atlantic salmon. Significant differences in the behavior of the two mutant strains indicated that the two pilus systems are not redundant.